Genetic Diversity of Croatian Common Bean Landraces - Carović-Stanko, Klaudija; Liber, Zlatko; Vidak, Monika; Barešić, Ana; Grdiša, Martina; Lazarević, Boris; Šatović, Zlatko (Frontiers in Plant Science, 2017)
In Croatia, the majority of the common bean production is based on local landraces, grown by small-scale farmers in low input production systems. Landraces are adapted to the specific growing conditions and agro-environments and show a great morphological diversity. These local landraces are in danger of genetic erosion caused by complex socio-economic changes in rural communities. The low profitability of farms and their small size, the advanced age of farmers and the replacement of traditional landraces with modern bean cultivars and/or other more profitable crops have been identified as the major factors affecting genetic erosion. Three hundred accessions belonging to most widely used landraces were evaluated by phaseolin genotyping and microsatellite marker analysis. A total of 183 different multi-locus genotypes in the panel of 300 accessions were revealed using 26 microsatellite markers. Out of 183 accessions, 27.32% were of Mesoamerican origin, 68.31% of Andean, while 4.37% of accessions represented putative hybrids between gene pools. Accessions of Andean origin were further classified into phaseolin type II (“H” or “C”) and III (“T”), the latter being more frequent. A model-based cluster analysis based on microsatellite markers revealed the presence of three clusters in congruence with the results of phaseolin type analysis.